The Programming of Antioxidant Capacity, Immunity, and Lipid Metabolism in Dojo Loach (Misgurnus anguillicaudatus) Larvae Linked to Sodium Chloride and Hydrogen Peroxide Pre-treatment During Egg Hatching - Wang, Mengya; Xu, Wenyu; Zou, Jiahong; Li, Shuaitong; Song, Zixi; Zheng, Feifei; Ji, Wei; Xu, Zhen; Wang, Qingchao (Frontiers in Physiology, 2021)
Non-nutritional stress during early life period has been reported to promote the metabolic programming in fish induced by nutritional stimulus. Sodium chloride (NaCl) and hydrogen peroxide (H2O2) have been widely applied during fish egg hatching, but the influences on health and metabolism of fish in their later life remain unknown. In the present study, H2O2 treatment at 400 mg/L but not 200 mg/L significantly increased the loach hatchability and decreased the egg mortality, while NaCl treatment at 1000 and 3000 mg/L showed no significant influences on the loach hatchability nor egg mortality. Further studies indicated that 400 mg/L H2O2 pre-treatment significantly enhanced the antioxidant capacity, and the mRNA expression of genes involved in immune response of loach larvae, accompanied with the increased expression of genes involved in fish early development. However, the expression of most genes involved in lipid metabolism including catabolism and anabolism of loach larvae were significantly up-regulated after 200 mg/L H2O2 pre-treatment. NaCl pre-treatment also increased the expression of antioxidant enzymes, however, only the expression of C1q within the detected immune-related genes was up-regulated in loach larvae. 1000 mg/L NaCl pre-treatment significantly increased the expression of LPL and genes involved in fish early development. Thus our results suggested the programming roles of 400 mg/L H2O2 pre-treatment during egg hatching in enhancing antioxidant capacity and immune response of fish larvae via promoting fish early development.